2018
DOI: 10.3390/toxins10080331
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxins from a Pharmacopoeial Point of View

Abstract: A pyrogen is a substance that causes fever after intravenous administration or inhalation. Gram negative endotoxins are the most important pyrogens to pharmaceutical laboratories. In the International, United States, Japanese and European Pharmacopoeias, there are two official methods to evaluate pyrogenicity—that is, the bacterial endotoxin test, and the pyrogen test. The main objective of this review is to compare the monographs of each test among the different Pharmacopeias, to detect similarities and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Some of these toxins are used in a medical context such as Botox; however, an unintended ingestion is likely to cause health issues ranging from fever to death. [ 1,45,117 ]…”
Section: Thermal Sterilizationmentioning
confidence: 99%
“…Some of these toxins are used in a medical context such as Botox; however, an unintended ingestion is likely to cause health issues ranging from fever to death. [ 1,45,117 ]…”
Section: Thermal Sterilizationmentioning
confidence: 99%
“…Over the last few decades, the detection methods of LPS have been continuously developed. Previous methods, such as the rabbit pyrogen test (RPT) [ 91 ], the Limulus amoebocyte lysate (LAL) [ 92 ], the monocyte activation test (MAT) [ 93 ], the recombinant factor C (rFC) [ 94 ], and the EndoLISA [ 95 ], cannot be routinely used to analyze clinical sepsis samples because of their disadvantages of temperature dependence, high cost, inconsistent, and long testing time. However, studies have shown that the LPS test methods based on aptamers were used for the early diagnosis of sepsis in the past few years, which have the advantages of sensitivity, specificity, high affinity, low cost, and time-saving.…”
Section: Aptamer-based Detection Of Sepsis-related Biomarkersmentioning
confidence: 99%
“…Pyrogen test measuring the increase of temperature in rabbits after intravenous injection of sterile tested solution [42,43].…”
Section: Rabbit Pyrogen Test (Rpt)mentioning
confidence: 99%